If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + -7 + 3h = 4(h + -12) Reorder the terms: -7 + 6h + 3h = 4(h + -12) Combine like terms: 6h + 3h = 9h -7 + 9h = 4(h + -12) Reorder the terms: -7 + 9h = 4(-12 + h) -7 + 9h = (-12 * 4 + h * 4) -7 + 9h = (-48 + 4h) Solving -7 + 9h = -48 + 4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4h' to each side of the equation. -7 + 9h + -4h = -48 + 4h + -4h Combine like terms: 9h + -4h = 5h -7 + 5h = -48 + 4h + -4h Combine like terms: 4h + -4h = 0 -7 + 5h = -48 + 0 -7 + 5h = -48 Add '7' to each side of the equation. -7 + 7 + 5h = -48 + 7 Combine like terms: -7 + 7 = 0 0 + 5h = -48 + 7 5h = -48 + 7 Combine like terms: -48 + 7 = -41 5h = -41 Divide each side by '5'. h = -8.2 Simplifying h = -8.2
| -4=-2w-7 | | 8w+3=5w-18 | | 4x+1+19x=11 | | 6m+8=2m-12 | | 9t-7=3t-5 | | 20y-6=18y+4 | | 4(6a+2)=-88 | | -2(3s-3)-6=-3(6s+0)-5 | | 3(-6t+4)=-5t+2(t-9) | | 14+b=13-3b | | 12x^4=2x^2+4 | | 2ysquare=12y-5y | | 4y+3=127 | | X^2-9y^2+6x-36y-36=0 | | 10=(6+9b)+7b | | 3log(2)=9log(x) | | x+6=4x-21 | | 6x+8+2x+4= | | 5.36-0.4m=26.8-0.4m | | 3(4x+3)+4x=61 | | (35-2x)(70-2x)= | | Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x | | 2x-5/7=8/25 | | x+(-16)=-12 | | nx=3y-5 | | 2/3(m-8)=9 | | 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p |